Reactivity of free radical intermediates that form spontaneously during molecular chlorine action on acetylene and vinyl monomers at low temperatures - Gordon, D.A.; Volodina, V.A.; Mikhailov, A.I. (Физика низких температур, 2013)
In this study ESR, UV, VIS and IR spectroscopy, chromatography, calorimetry, and elemental analysis were
employed to show the spontaneous formation of free radicals under low-temperature action of molecular chlorine
on acetylene monomer p-diethynylbenzene, and vinyl monomer acrylamide. These radicals are able to initiate
chain reaction of polymerization of monomers at low temperatures. This reaction results in a completely
soluble polymer with a yield of 25 %, while an insoluble cross-linked polymer has been obtained during polymerization
of p-diethynylbenzene initiated by other means. For example, under radiolysis by 1000 kGy the soluble
fraction of obtained polymer was ≈ 1% while the overall yield was ≈ 10%. p-Diethynylbenzene polymerizes at
temperatures close to chlorine melting (170 K). Polymerization of acrylamide takes place in the temperature
range of 180–210 K with an yield of polymer ≈ 10%. The low-temperature chlorination of a 20%-solution of
acrylamide in glycerol enables a twofold increase of the polymer yield, and a tenfold decrease of the chlorine
content in it.